2016
DOI: 10.3390/rs8110886
|View full text |Cite
|
Sign up to set email alerts
|

Forest Fragmentation in the Lower Amazon Floodplain: Implications for Biodiversity and Ecosystem Service Provision to Riverine Populations

Abstract: This article analyzes the process of forest fragmentation of a floodplain landscape of the Lower Amazon over a 30-year period and its implications for the biodiversity and the provision of ecosystem services to the riverine population. To this end, we created a multi-temporal forest cover map based on Landsat images, and then analyzed the fragmentation dynamics through landscape metrics. From the analyses of the landscape and bibliographic information, we made inferences regarding the potential impacts of frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 91 publications
0
20
0
1
Order By: Relevance
“…The annual river flood pulse is monomodal and varies in average 5.7 m creating marked differences in floodplain conditions between high‐water periods, when most areas are flooded, and low‐water periods when only lakes and connecting channels retain water. Historically, large areas of várzea were deforested for agriculture and cattle ranching, which led to a loss of 56% of floodplain forest cover by 2008 in the Lower Amazon (Renó et al., ) and to fragmentation of the remaining forest (Renó, Novo, & Escada, ). Over the past 30 years, 79% of the deforested area was replaced with herbaceous vegetation, 5% is bare soil where ground cover has not yet regenerated and 16% is open water in channels widened through bank erosion (Renó et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The annual river flood pulse is monomodal and varies in average 5.7 m creating marked differences in floodplain conditions between high‐water periods, when most areas are flooded, and low‐water periods when only lakes and connecting channels retain water. Historically, large areas of várzea were deforested for agriculture and cattle ranching, which led to a loss of 56% of floodplain forest cover by 2008 in the Lower Amazon (Renó et al., ) and to fragmentation of the remaining forest (Renó, Novo, & Escada, ). Over the past 30 years, 79% of the deforested area was replaced with herbaceous vegetation, 5% is bare soil where ground cover has not yet regenerated and 16% is open water in channels widened through bank erosion (Renó et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The study area is located between the Trombeta River mouth to the west (close to Paru Lake) and Monte Alegre city to the east (Figure 1), a region representative of the lower Amazon floodplain which is characterized by large and shallow lakes [8]. The region is exposed to an extreme fragmentation of the floodplain forest, which the cover of has been reduced by 56% in the lasts 40 years (1975-2008) [10], being firstly occupied by jute farming and later by cattle ranching [17,20]. The large lakes in this region create local floodplain systems which the names of are associated with those lakes less affected by the water-level change along the hydrological year.…”
Section: Study Areamentioning
confidence: 99%
“…Under the pressure of anthropogenic factors [19,20] and climate changes [21,22], the monitoring of the sediment concentration patterns in Amazon floodplains becomes a key indicator of the basin resilience to those impacts. As Total Suspended Solids (TSS) fluxes are fundamental to biogeochemical processes and to the biodiversity of floodplains, their spatial and temporal dynamics have been the object of several studies [6][7][8]13,16,[23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial ecosystems not only continuously provide food, fiber, fuel, and other products for humans, but also simultaneously supply public goods that cannot be delivered by the market, such as climate regulation, hydrology regulation, waste regulation, soil conservation, and aesthetic landscape provision, bringing substantial welfare to human [8,9,49]. This could cause ecosystems to have high environmental load and low sustainability, purely for the purpose of economic development and personal needs [23,50]. In this study, the results of the moving weighted trend surface analysis showed that the ESV losses pattern of the agro-pastoral ecotone was similar to an “inclined surface”, i.e., the northeastern section of the ecotone lost more ESV than the other sections.…”
Section: Discussionmentioning
confidence: 99%